Bacterial translocation in patients with liver cirrhosis: physiology, clinical consequences, and practical implications. (3rd July 2018) - Ponziani, Francesca Romana; Zocco, Maria Assunta; Cerrito, Lucia; Gasbarrini, Antonio; Pompili, Maurizio
ABSTRACT: Introduction : The gut liver axis is an operative unit that works to protect the human body against potentially harmful substances and microorganisms, maintaining the homeostasis of the immune system. Liver cirrhosis profoundly alters this complex system. The intestine becomes more permeable allowing the translocation of bacteria, bacterial products and fragments into the portal circulation, triggering an abnormal local and systemic inflammatory response and a condition of perpetual immunologic alarm. This immune-inflammatory disorder related to dysbiosis is involved in the development of liver damage and liver cirrhosis complications and increases intestinal permeability in a vicious circle. Areas covered : The most relevant studies on bacterial translocation, the mechanism of intestinal barrier dysfunction and its consequences in patients with liver cirrhosis have been revised through a PubMed search. Data have been discussed with particular regard to their significance in clinical practice. Expert commentary : The assessment of bacterial translocation and intestinal permeability is not currently used in clinical practice but may be useful to stratify patients' prognosis.